PREMIUM SPEAKING CARDS IS RESILIENCE STRATEGIES IN TEACHING LEAPING INTO THE MODERN ERA - Amran, Ali (UIN Sumatera Utara, 2023)
Teaching and learning a language are one of the professional processes of transferring some conscious knowledge from the teachers to learners. Teachers must prepare what knowledge of a particular lesson they are going to transfer to their learners. That is why they need some resilience teaching techniques and related or current teaching materials, design best teaching plans and search and gather best teaching references and apply the resilience teaching strategies to their learners especially in teaching foreign language. As an academic activity, in terms of teaching and learning processes, learners have their own targets to learn a foreign language, for example, to pass the exam managed either by state or private institution. The problem is that we have to know the reasons and the purposes what we learn a new language for. There are so many reasons why people learn a language. Thereof it is very important now for both language teachers and language learners to be able to distinguish between learning a language and learning about the language. This study tries to investigate how the resilience teaching strategy works in learning a language by applying Premium Speaking Cards as one of the teaching medias. Dealing with the research methodology, this study uses a qualitative method. The results of the research shows that premium speaking card game should be applied by language teachers to their leaners in order to gain their speaking quality and the resilience teaching strategies for the teachers, let alone in leaping into an extraordinary era.